Playful activities to do with babies from 8 months to two years old (Research, Society and Development, 2022)
In this, the objective was to identify the playful activities to develop with babies from 8 months to two years of age - making use of games, toys and materials of our day-to-day, seeking the development of the learning of babies and children since a very long time. new. As research methods, the literature review with the following subjects was used: games and toys for babies, playing in the nursery, activities for nursery 1 and 2, activities for nursery 1 and 2, recreational and educational activities, among others. . Through the accomplishment of this research it is concluded that: the games, the toys and develop a work more focused on playfulness the baby or the child can develop better, learn things better, sharpen curiosity, imagination, improve movements, motor coordination, dexterity, that is, everything in the most fun and much more pleasurable way.